Workers' voice: Transnational companies - a concern for strong workers' voice (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2019)
Trade is important to European companies as they export goods worth EUR 1.74 trillion each year. However, economic openness is under attack; populist movements are on the rise. Indeed, national regulation becomes less effective as companies become more and more transnational. As global governance is missing, Global Framework Agreements (GFAs) between transnational companies and global trade unions are one way to shape globalization and promote labor rights around the globe.
Keywords: 330; Workers' Voice